Hsa-miR-557 Inhibits Osteosarcoma Growth Through Targeting KRAS - Qiao, Zhi; Li, Jinfeng; Kou, Hongwei; Chen, Xiangrong; Bao, Deming; Shang, Guowei; Chen, Songfeng; Ji, Yanhui; Cheng, Tian; Wang, Yisheng; Liu, Hongjian (Frontiers in Genetics, 2022)
Objective: Osteosarcoma is the most common malignancy in the skeletal system; studies showed an important role of miRNAs in tumorigenesis, indicating miRNAs as possible therapeutic molecules. This study found abnormal hsa-miR-557 expression levels in osteosarcoma and tried to explore the potential function and the mechanism. Methods: Differential expression genes of osteosarcoma were analyzed using GSE28423 from the GEO database. Survival analysis of miRNAs was conducted with data obtained from the TARGET-OS database. STRING and miRDIP were used to predict target genes of hsa-miR-557; KRAS was then verified using dual-luciferase reporter assay. Expression of genes was detected by qPCR, and levels of proteins were detected by Western blot. The proliferation ability of cells was detected by CCK-8 and cell cycle analysis. Tumor formation assay in nude mice was used to detect the influence of osteosarcoma by hsa-miR-557 in vivo. Results: Analysis from the GEO and TARGET databases found 12 miRNAs that are significantly related to the osteosarcoma prognosis, 7 downregulated (hsa-miR-140-3p, hsa-miR-564, hsa-miR-765, hsa-miR-1224-5p, hsa-miR-95, hsa-miR-940, and hsa-miR-557) and 5 upregulated (hsa-miR-362-3p, hsa-miR-149, hsa-miR-96, hsa-miR-744, and hsa-miR-769-5p). CCK-8 analysis and cell cycle analysis found that hsa-miR-557 could significantly inhibit the proliferation of osteosarcoma cells. The tumor formation assay in nude mice showed that tumor sizes and weights were inhibited by hsa-miR-557 transfection. Further studies also proved that hsa-miR-557 could target the 3′UTR of KRAS and modulate phosphorylation of downstream proteins. Conclusion: This study showed that hsa-miR-557 could inhibit osteosarcoma growth both in vivo and in vitro, by modulating KRAS expression.